Determinação da matéria mineral por tratamento térmico e dos teores de formas de enxofre por peroxidação do carvão brasileiro - Fallavena, Vera Lucia Vargas (2011)
The Brazilian coal has about 50% ash and high sulfur content is usually classified as a low rank. Information about the mineral and organic fractions of coal, through a series of analytical characterization techniques are essential for its sustainable use. In this study, the content of mineral matter (MM) in Brazilian coal, was obtained from the ash content of medium temperature (300°C, 400°C and 370°C) and low temperature (<200°C) with oxygen plasma (LTA) with the purpose to isolate the MM without the changes caused by high temperatures (775°C) and analyze it without the interference caused by organic matter. Due to environmental problems caused by sulfur in the coal, peroxidation was evaluated as a desulfurization process and estimation of the contents of sulfur forms in coals. The results shows that the percentage of MM obtained at 300°C and LTA are approximately 8 to 17% higher than ash contents obtained at high temperatures. The process of peroxidation in hydrochloric acid media showed to be a technique that can be applied to the desulfurization of coal by removal of 86% to 98% of pyritic sulfur. The concentration of sulphate in the extracts can be used to predict the total sulfur (≤ 14% error) for samples with lower relative levels of organic sulfur (<30% Stotal). The sum of the pyritic and sulfate sulfur can also be estimated from the levels of dissolved sulfate, with errors less than 14% for most of the coals studied. Measurements of iron content gives an indication of the amount of pyrite present, with an error of ±12%.